Ectopic Lignification in the Flax lignified bast fiber1 Mutant Stem Is Associated with Tissue-Specific Modifications in Gene Expression and Cell Wall Composition . Issue 11 (7th November 2014) - Chantreau, Maxime; Portelette, Antoine; Dauwe, Rebecca; Kiyoto, Shingo; Crônier, David; Morreel, Kris; Arribat, Sandrine; Neutelings, Godfrey; Chabi, Malika; Boerjan, Wout; Yoshinaga, Arata; Mesnard, François; et al.
Abstract : The cell walls of flax bast fibers contain high cellulose and low lignin levels, imparting tensile strength and flexibility. To learn more about the mechanisms responsible for this type of cell wall structure, a collection of ectopic lignin mutants was identified. Characterization of the lbf1 mutant provided key information on lignification in flax that is also relevant to other plants. Abstract: Histochemical screening of a flax ethyl methanesulfonate population led to the identification of 93 independent M2 mutant families showing ectopic lignification in the secondary cell wall of stem bast fibers. We named this core collection the Linum usitatissimum (flax) lbf mutants for lignified bast fibers and believe that this population represents a novel biological resource for investigating how bast fiber plants regulate lignin biosynthesis. As a proof of concept, we characterized the lbf1 mutant and showed that the lignin content increased by 350% in outer stem tissues containing bast fibers but was unchanged in inner stem tissues containing xylem. Chemical and NMR analyses indicated that bast fiber ectopic lignin was highly condensed and rich in G-units. Liquid chromatography-mass spectrometry profiling showed large modifications in the oligolignol pool of lbf1 inner- and outer-stem tissues that could be related to ectopic lignification. Immunological and chemical analyses revealed that lbf1 mutants also showed changes to other cell wall polymers. Whole-genome transcriptomics suggested that ectopic lignification of flax bast fibers could be caused by increased transcript accumulation of (1) the cinnamoyl-CoA reductase, cinnamyl alcohol dehydrogenase, and caffeic acid O-methyltransferase monolignol biosynthesis genes, (2) several lignin-associated peroxidase genes, and (3) genes coding for respiratory burst oxidase homolog NADPH-oxidases necessary to increase H2 O2 supply.